2019
DOI: 10.1111/jvp.12774
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and relative bioavailability of tiamulin in broiler chicken as influenced by different routes of administration

Abstract: The bioavailability and pharmacokinetic disposition of tiamulin in broiler chicken were investigated after administration through the crop, drinking water, and feed at 40 mg/kg body weight. Residues of tiamulin in tissues of broiler chicken were also assessed. Plasma and tissue concentrations of tiamulin were analyzed by reverse‐phase high‐performance liquid chromatography (HPLC) method. Plasma concentration–time data were described by the non‐compartmental model for all three routes, and pharmacokinetic param… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 12 publications
(22 reference statements)
4
13
2
1
Order By: Relevance
“…The findings of this study revealed that tiamulin, when administered orally to ducks, was rapidly absorbed with C max values [0.77 and 2.32 µg/mL attained at 2 h (T max ) for 30 and 60 mg/kg, respectively] and these values were similar to those reported for dogs, goats, and ewes, which were injected with tiamulin intramuscularly (i.m.) at 10 mg/kg (0.60, 0.56, and 0.64 µg/mL, respectively) (14, 37), pig administered tiamulin orally at 10 mg/kg (0.69 µg/mL) (13), chickens received tiamulin orally at 40 mg/kg (0.73 µg/mL reached at 1.5 h) (16), and for chickens injected with tiamulin i.m. at 5 mg/kg (2.05 µg/mL) and 40 mg/kg (8.8 µg/mL) (15).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The findings of this study revealed that tiamulin, when administered orally to ducks, was rapidly absorbed with C max values [0.77 and 2.32 µg/mL attained at 2 h (T max ) for 30 and 60 mg/kg, respectively] and these values were similar to those reported for dogs, goats, and ewes, which were injected with tiamulin intramuscularly (i.m.) at 10 mg/kg (0.60, 0.56, and 0.64 µg/mL, respectively) (14, 37), pig administered tiamulin orally at 10 mg/kg (0.69 µg/mL) (13), chickens received tiamulin orally at 40 mg/kg (0.73 µg/mL reached at 1.5 h) (16), and for chickens injected with tiamulin i.m. at 5 mg/kg (2.05 µg/mL) and 40 mg/kg (8.8 µg/mL) (15).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the present study showed a second peak at 8 h post-tiamulin administration with the two different doses. This is likely due to the enterohepatic recycling of tiamulin during biliary elimination (15,16). In addition, following oral administration of tiamulin at 30 mg/kg, the AUC extrapolated to infinity was 5.85 µg * h/mL.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations